Phase II Study of Everolimus in Metastatic Malignant Melanoma (NCCTG‐N0377, Alliance). (17th April 2018) - Vera Aguilera, Jesus; Rao, Ravi D.; Allred, Jacob B.; Suman, Vera J.; Windschitl, Harold E.; Kaur, Judith S.; Maples, William J.; Lowe, Val J.; Creagan, Edward T.; Erickson, Lori A.; Markovic, Svetomir
Abstract : Lessons Learned : Everolimus does not have sufficient activity to justify its use as single agent in metastatic melanoma. Patients treated with 10 mg per day dose were most likely to require dose reductions. Everolimus appeared to reduce the numbers of regulatory T cells in approximately half of the treated patients; unfortunately, these effects were not correlated with clinical outcomes. Background: Everolimus (RAD‐001) is an orally active rapamycin analogue shown in preclinical data to produce cytostatic cell inhibition, which may be potentially beneficial in treating melanoma. We conducted a phase II study to evaluate the efficacy and safety of everolimus in patients with unresectable metastatic melanoma (MM). Methods: This study included two cohorts; cohort 1 received 30 mg of everolimus by mouth (PO) weekly, and cohort 2 was dosed with 10 mg of everolimus PO daily. The endpoints of the study were safety, 16‐week progression‐free survival (PFS), overall survival (OS), and measures of immunomodulatory/antiangiogenic properties with therapy. Tumor samples before therapy and at week 8 of treatment were analyzed. Peripheral blood plasma or mononuclear cell isolates collected prior to therapy and at weeks 8 and 16 and at time of tumor progression were analyzed for vascular endothelial growth factor and regulatory T‐cell (Treg) measurements. Results: A total of 53 patients were enrolled in cohort 1 ( n = 24) and cohort 2 ( n = 29). Only 2 patients of the first 20 patients enrolled in cohort 2 had treatment responses (25%; 95% confidence interval, 8.6%–49.1%); this result did not allow full accrual to cohort 2, as the study was terminated for futility. Median OS was 12.2 months for cohort 1 versus 8.1 months in cohort 2; no PFS advantage was seen in either group (2.1 months vs. 1.8 months). Dose‐limiting toxicities included grade 4 myocardial ischemia (3.4%); grade 3 fatigue, mucositis, and hyperglycemia (10.3%); and anorexia and anemia (6.9%). Everolimus significantly reduced the number of Tregs in approximately half of the treated patients; however, these effects were not correlated with clinical outcomes. Conclusion: Everolimus does not have sufficient single‐agent activity in MM; however, we have identified evidence of biological activity to provide a potential rationale for future combination studies.